Fracture mechanics: for modern engineering design - Simha,K.R.Y (University Press, 2001)
Fracture mechanics: for modern engineering design / Simha,K.R.Y.. -- New Delhi: University Press, 2001 531.1 Si651 No. of Copies : 1